Limitasi UU Partai Politik Dalam Mendorong Partisipasi Politik Perempuan di Indonesia: Kajian Hukum dan Perubahan Sosial - Layyin Mahfiana (Justicia Islamica, 2011)
This paper tries to study two main things, first: whether women's involvement in the political sector is the real participation of women or just another form of politicization of women, second: whether state policies toward women affect society paradigm in looking at women. Two questions are based on the fact that  the involvement of women in political leadership is still weak and public perception about women is still dominated by patriarchal culture that resulted in the subordination of women in the political sector.